2019
DOI: 10.1002/vjch.201900081
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the antioxidant potential of thiamine: Thermochemical and kinetics studies in aqueous phase using DFT

Abstract: The scavenging mechanism of thiamine (or vitamin B1) towards HO  and HOO  radicals has been revisited using density functional theory (DFT) at the M05-2X/6-311++G (d,p) level of theory. Enthalpies and Gibbs free energies of four common antioxidant reactions, i.e. formal hydrogen transfer (FHT), proton transfer (PT), single electron transfer (SET) and radical adduct formation (RAF), have been systematically calculated in the aqueous phase. Potential energy profiles accompanied with the optimized structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…In comparison with the lowest BDEs of other potential antioxidant like α-terpinene (74.4 kcal mol −1 in the gas phase), thiamine (85.7, 88.3, and 86.7 kcal mol −1 ), 89 Trolox (76.6, 78.4, and 76.6 kcal mol −1 ), and ascorbic acid (73.4, 79.0, and 74.5 kcal mol −1 ) calculated at the same computational approaches in the gas phase, water, and PEA, respectively, compounds C3, C4, and C5 represent promising antioxidants via the HT process.…”
Section: Preliminary Evaluation Of Antioxidant Potential Via Dpphmentioning
confidence: 99%
“…In comparison with the lowest BDEs of other potential antioxidant like α-terpinene (74.4 kcal mol −1 in the gas phase), thiamine (85.7, 88.3, and 86.7 kcal mol −1 ), 89 Trolox (76.6, 78.4, and 76.6 kcal mol −1 ), and ascorbic acid (73.4, 79.0, and 74.5 kcal mol −1 ) calculated at the same computational approaches in the gas phase, water, and PEA, respectively, compounds C3, C4, and C5 represent promising antioxidants via the HT process.…”
Section: Preliminary Evaluation Of Antioxidant Potential Via Dpphmentioning
confidence: 99%
“…Enthalpies and Gibbs free energies of four common antioxidant reactions, i.e., formal hydrogen transfer (FHT), proton transfer (PT), single electron transfer (SET) and radical adduct formation (RAF), have been calculated but in the aqueous phase. The results showed that in comparing with trolox and ascorbic acid, their antioxidant potential has been classified in the decreasing order: ascorbic acid > thiamine > trolox [13]. Preliminary studies indicated the existence of certain correlations between the activity of antioxidants and the content of vitamins [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the metabolic and structural function, thiamine has also demonstrated antioxidant properties. Thiamine as scavenger of ROS removes hydroxyl (HO • ) radical significantly higher than hydroperoxyl radical (HOO • ) [ 113 ].…”
Section: The Antioxidant Protective Role Of Thiaminementioning
confidence: 99%